Theory of noise suppression in Λ-type quantum memories by means of a cavity - Nunn, JAS; Munns, JHD; Thomas, SE; Kaczmarek, KT; Qiu, C; Feizpour, A; Poem, E; Brecht, B; Saunders, DJ; Ledingham, PM; Reddy, DV; Raymer, MG; et al. (American Physical Society, 2018)
Quantum memories, capable of storing single photons or other quantum states of light, to be retrieved on demand, offer a route to large-scale quantum information processing with light. A promising class of memories is based on far-off-resonant Raman absorption in ensembles of Λ-type atoms. However, at room temperature these systems exhibit unwanted four-wave mixing, which is prohibitive for applications at the single-photon level. Here, we show how this noise can be suppressed by placing the storage medium inside a moderate-finesse optical cavity, thereby removing the main roadblock hindering this approach to quantum memory.